Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens?. Issue 4 (24th February 2023) - Pothineni, Bhanu Kiran; Keller, Adrian
Abstract : The occurrence and spreading of multidrug resistance in bacterial pathogens represent one of the greatest challenges of the 21st century. With fewer and fewer new antibiotics in development, novel and unconventional concepts in drug development and formulation need to be explored to overcome the global antibiotics crisis. Biomedical nanotechnology offers promising strategies for the reformulation of established antibiotics in such a way that they regain their activity against resistant pathogens. Herein, promising developments aimed at the synthesis of potent nanoparticle‐based formulations of glycopeptide antibiotics are reviewed. While glycopeptide antibiotics such as vancomycin and teicoplanin are widely used as drugs of last resort against Gram‐positive pathogens such as methicillin‐resistant Staphylococcus aureus (MRSA), bacterial resistance against these drugs is spreading. However, inhibiting cell wall synthesis via binding to cell wall precursor peptidoglycans, glycopeptide antibiotics exhibit a unique mode of action that renders them particularly promising candidates for nanoparticle‐based formulations with the ability to overcome glycopeptide antibiotic resistance. Herein, different formulation concepts based on multivalent presentation and encapsulation are introduced, different synthesis and conjugation strategies are discussed, and an attempt is made to rationalize their effects on the antibacterial activity of the resulting nanoparticle formulations. Abstract : The rapid worldwide spreading of antimicrobial resistance (AMR) in bacterial pathogens represents an epic threat to human health and new strategies for overcoming AMR are urgently needed. Herein, different nanoparticle‐based formulations of the cell‐wall‐targeting glycopeptide antibiotics vancomycin and teicoplanin are reviewed and their potential of regaining antibacterial activity against resistant bacteria is discussed.